Renal and testicular up-regulation of pro-inflammatory chemokines (RANTES and CCL2) and cytokines (TNF-α, IL-1β, IL-6) following acute edible camphor administration is through activation of NF-kB in rats - Oluwatobi T. Somade; Babajide O. Ajayi; Oluwaseyi A. Safiriyu; Oluwasola S. Oyabunmi; Adio J. Akamo (Toxicology Reports, 2019)
Camphor-induced oxidative stress and histopathological changes (in brain, lung, liver, kidney and testes) have been reported. We therefore investigated the effect of various doses of camphor in an acute study, on renal and testicular levels of some pro-inflammatory mediators in male wistar rats. Twenty rats divided into four groups of five rats each were used in this study. Group 1 served as control and was administered 6 mL/kg olive oil, the vehicle for camphor, while groups 2, 3 and 4 were orally administered 1000, 2000, and 4000 mg/kg body weight camphor, for seven days. Compared with control, levels of tumor necrosis factor alpha (TNF-α), interleukin 1 beta (IL-1β) and interleukin 6 (IL-6) were significantly increased kidney and testes by 2000 and 4000 mg/kg body weight, while interleukin 10 (IL-10) was only significantly increased by 1000 mg/kg body weight of camphor in both tissues. Also compared with control, all doses of camphor administered resulted in a significant increase in the expressions of renal and testicular nuclear factor kappa B (NFkB), cyclooxygenase 2 (COX-2), regulated upon activation normal T cell expressed and secreted (RANTES), and monocyte chemo-attractant protein 1 (MCP-1). Conclusively, use and consumption of camphor should be with caution as it could trigger renal and testicular inflammation through activation of NF-kB and up-regulation of pro-inflammatory markers. Keywords: Camphor, Chemokines, Cytokines, Pro-inflammation, Renal, Testicular